Aquinas at 800 - Papers from the 2024 Notre Dame Conference: Revisiting Human Law's Capacity to Cultivate Moral Virtue - Lemos, Catherine (European journal for the study of Thomas Aquinas, 2025)
This article offers a new perspective on the topic of human-made law's capacity to cultivate moral virtue by focusing on two questions. First, is cultivating an individual's virtue part of the goal of law or only a concomitant effect? Secondly, can our laws play a constructive role in fostering virtues beyond discouraging vices? To the first question, I will intervene in the debate between John Finnis and his interlocutors over the nature of the common good. To the second question, I will show how human law can contribute to key aspects of growth in virtue and thereby poise us to develop habits.